Boron and nitrogen co-doped porous carbon with a high concentration of boron and its superior capacitive behavior. (March 2017) - Chen, Hao; Xiong, Yachao; Yu, Tao; Zhu, Pengfei; Yan, Xinzhu; Wang, Zhao; Guan, Shiyou
Abstract: In this work, boron and nitrogen co-doped hierarchical porous carbon (BN-HPC) with a relatively high contents of boron (3.97 wt%) and nitrogen (12.10 wt%) is synthesized by a method combined with template process and carbonization of hierarchical porous resin using melamine and boric acid as nitrogen and boron sources, respectively. The co-doping method achieves a high boron doping level (8 times of that of single boron doped sample) which is of great significance in increasing the doping efficiency of boron. The hierarchical porosity, structure and surface chemical properties are studied in detail via various means, such as Transmission Electron Microscopy, N2 sorption, X-ray diffraction, X-ray photoelectron spectroscopy and elemental analysis, etc. Owing to the synergistic effect of hierarchical porosity and heteroatoms doping, BN-HPC exhibits greatly improved electrochemical capacitive performance of 304 F g −1 at a current density of 0.1 A g −1 and good rate capability (189 F g −1 remained at a current density of 10 A g −1 ). The strategy of synthesis is facile and very effective. Graphical abstract: